PERANAN DIREKTORAT RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH RIAU DALAM PENEGAKAN HUKUM TERHADAP PASAL 17 AYAT (2) HURUF B UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN - Yakub Frans Sihombing; Erdianto Effendi; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Indonesia is a rich country. Riau Province is one of the areas that have natural resources and non-biological abundant, and the forest is one of the riches contained in it. The extent of forest area in the province is directly proportional to the number of forestry crime happened. One of the criminal act occurred, ie forestry plantation activities without permission minister in forest areas under Article 17 Paragraph (2) Letter B Act No. 18 of 2013 concerning the Prevention and Combating Deforestation and criminal sanctions provided for in Article 92 Paragraph (1). Throughout 2014 there has been a 5 cases of this criminal act. Ditreskrimsus Police in Riau as one of the law enforcement agency should be able to run perananya properly and optimally so as to suppress and reduce the occurrence of such crime. The purpose of this thesis are: First, What is the role Ditreskrimsus Riau Regional Police in enforcement of Article 17 Paragraph (2) Letter b Law No. 18 Year 2013. Secondly, Is Ditreskrimsus barriers Riau Regional Police in enforcement of Article 17 Paragraph (2) Letter b Law No. 18 Year 2013. Third, How are Ditreskrimsus Police in Riau in overcoming barriers to enforcement of Article 17 Paragraph (2) Letter b Law No. 18 Year 2013 concerning the Prevention and Eradication of forest destruction.The research results can be concluded first, Role conducted by Ditreskrimsus Riau Regional Police in law enforcement against criminal acts plantation activities without permission minister in the forest in Riau Province is by taking action preemptive, preventive, and repressive. Second, obstacles encountered in implementing the law enforcement include: financial barriers (financial), lack of facilities and infrastructure barriers, lack of human resources law enforcement officials, community barriers and factors territory. Third, efforts made by Ditreskrimsus Police in Riau to overcome obstacles in law enforcement is to propose the addition of operating costs, cooperation and coordination with other relevant agencies, improve the delivery of public education about the forest and the applicable law and to reform internally.Keywords: Role-Enforcement-Plantation-Forest Area